Open Government Data in Pandemic Disease: Encouraging Spatial Policy-Making in East Java and Jakarta - Arga Pribadi Imawan; Rifqi Fathurrahman (Departemen Administrasi Publik, Universitas Diponegoro, 2022)
This article aims to elaborate on whether the openness of spatial data by the government has an implication for the formulation of government policies. The case was taken in two provinces, namely the East Java provincial and the Special Capital Region (DKI) Jakarta. The case study method was conducted by referring to a database of documents, journals, news and books relating to the spatial data visualization and provincial government policies. ArcGis application is also used as one method of presenting data. As a result of the elaboration by using the concept of models open government data (OGD) and spatial policy-making, this article discovers facts that models of OGD in East Java are at the four-stage which is data integration between government and social data. However, DKI Jakarta shows the stage of OGD models is in integration government data stage. Both provincial showed that the policy-formulation for Covid-19 are not based on spatial data. Therefore, it can be assumed policy for handling Covid-19 is not effective. Both of provinces shows continually increasing cases of Covid-19 positive patients. These two provinces are predicated as the highest level of Covid-19 cases in Indonesia. From a practical point of view, Indonesia needs to implementing spatial data-based policies to break the Covid-19 chain, as this kind of policy orientation has been successfully implemented by Taiwan which has been successful tackling Covid-19.